A self-assembling polymer material for mesenchymal stem cell encapsulation and its preparation method and application
By using self-assembled polymer materials with hyaluronic acid backbone and short peptide side chains for in situ encapsulation on the cell surface, the equipment dependence and cytotoxicity problems in the prior art are solved, efficient and safe cell encapsulation is achieved, and cell activity is maintained and good biocompatibility is achieved.
Patent Information
- Application Number
- CN202410497170.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-23
- Filing Date
- 2024-04-24
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The prior art has problems with device dependence and cytotoxicity during cell encapsulation, with low encapsulation efficiency and reduced cell activity.
A self-assembled polymer material composed of hyaluronic acid backbone and short peptide side chain is used to adsorb and fix cells through targeted action, and encapsulate in situ on the cell surface through self-assembly motifs to form a mesh crosslinked structure.
Cell encapsulation under equipment-independent conditions is achieved, packaging efficiency and cell activity are improved, and the material has good biocompatibility.
Smart Images

Figure BDA0004807520280000021 
Figure FDA0005239838780000011 
Figure HDA0004807520290000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biological science technology, and specifically relates to a self-assembling polymer material for mesenchymal stem cell encapsulation and a preparation method and application thereof. Background Art
[0002] Cell surface encapsulation is a technology that wraps cells in an encapsulation layer such as a semipermeable membrane or hydrogel formed by a polymer. The encapsulation layer can effectively block direct contact between large external objects and encapsulated cells, avoiding attacks by immune cells and enzymes; it can also ensure the free exchange of small objects such as oxygen and nutrients, maintaining the biological activities and normal functions of cells. Cell surface encapsulation technology is believed to have great application prospects in sample processing at the single cell level and allogeneic cell transplantation.
[0003] At present, polymer materials for encapsulating cells are often formed by monomer polymerization. The formed encapsulation layer is not stable and has certain cytotoxicity. Therefore, finding encapsulation materials with good biocompatibility is an important development direction for cell encapsulation. Among them, natural polymer materials with high biocompatibility such as sodium alginate and hyaluronic acid are used as matrices. The cell encapsulation layer prepared by ion chelation and covalent crosslinking can maintain the normal growth and function of encapsulated cells. Therefore, the construction of coatings with natural polymers as matrices has become the research focus of cell encapsulation. At present, the methods for preparing cell coatings with natural polymer materials include the following: ① Microfluidic technology, using microfluidic devices to construct gel microspheres to achieve single cell encapsulation. David Mooney combined microfluidic devices with sodium alginate and successfully constructed a coating structure on the surface of mesenchymal stem cells (MSCs); ② Layer-by-layer self-assembly technology, usually using electrostatic attraction, molecular biorecognition, hydrogen bonding and other effects to alternately deposit two or even more polymers on the cell surface to form a polymer film, thereby achieving cell nanoencapsulation. David Mills adsorbed positively charged polylysine and negatively charged hyaluronic acid (HA) on the surface of a single MSC through electrostatic interaction. The encapsulated MSCs maintained the intact morphology and activity of the cells for more than a week.
[0004] Although the above-reported preparation methods successfully construct coating structures outside cells, there are technical disadvantages in the process: ① The microfluidic technology preparation method is equipment-dependent, and there is inevitably a "cell escape" phenomenon at the water-oil interface, resulting in low encapsulation efficiency; ② Polycations will destroy the phospholipid bilayer on the cell membrane surface, leading to the formation of pores on the cell surface, thereby releasing enzymes in the cytoplasm, causing cell activity to decrease or even die. Therefore, it is urgent to develop a safer, simpler and faster polymer material for encapsulating cells to solve the above technical problems. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a self-assembling polymer material, which can complete the adsorption and fixation of the material to cells through the targeting effect of hyaluronic acid without relying on equipment, and at the same time complete the in-situ encapsulation of the polymer on the cell surface with the help of self-assembling primitives.
[0006] The invention also provides a method for preparing the self-assembling polymer material.
[0007] The present invention also provides the application of the self-assembling polymer.
[0008] The invention also provides a self-assembled natural polymer nanofiber.
[0009] The invention also provides a polymer coating for cell encapsulation.
[0010] According to a first aspect of the present invention, a self-assembling polymer material is provided, comprising a hyaluronic acid main chain and short peptide side chains, wherein the self-assembling polymer material has the following structural formula:
[0011]
[0012] Among them, 248≤m≤319, 53≤n≤124.
[0013] According to a second aspect of the present invention, there is provided a method for preparing the self-assembling polymer material according to the first aspect of the present invention, comprising the following steps:
[0014] S1: dissolving hyaluronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in a solvent and reacting them sufficiently to obtain a hyaluronic acid solution;
[0015] S2: mixing the short peptide solution and the hyaluronic acid solution obtained in step S1 to obtain a reaction solution;
[0016] S3: dialyzing the reaction solution obtained in step S2, and collecting the liquid phase obtained after dialysis, which is the self-assembled polymer material.
[0017] In some embodiments of the present invention, the structure of the short peptide in step S2 includes: naphthyl-phenylalanine-phenylalanine-lysine-phosphorylated tyrosine residue.
[0018] In some embodiments of the present invention, the molar ratio of hyaluronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in step S1 is 1:(1-2):(1-2).
[0019] In some preferred embodiments of the present invention, the molar ratio of hyaluronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in step S1 is 2:3:3.
[0020] In some embodiments of the present invention, the solvent in step S1 includes formamide.
[0021] In some embodiments of the present invention, the hyaluronic acid in step S1 is first added to a solvent, and after being fully dissolved, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are added to react.
[0022] In some preferred embodiments of the present invention, the dissolution conditions of the hyaluronic acid after adding the solvent in step S1 include: stirring and dissolving at 40-70° C. for 0.5-2 h.
[0023] In some more preferred embodiments of the present invention, the dissolution conditions of the hyaluronic acid after adding the solvent in step S1 include: stirring and dissolving at 50° C. for 1 hour.
[0024] In some preferred embodiments of the present invention, the reaction conditions after adding EDC and NHS to the solvent in step S1 include: reacting at 0-5° C. for 20-40 min.
[0025] In some more preferred embodiments of the present invention, the reaction conditions after adding EDC and NHS to the solvent in step S1 include: reacting at 0° C. for 30 min.
[0026] In some embodiments of the present invention, the solvent of the short peptide solution in step S2 is selected from at least one of formamide, N,N-dimethylformamide, and dimethyl sulfoxide.
[0027] In some preferred embodiments of the present invention, the solvent of the short peptide solution in step S2 is N,N-dimethylformamide.
[0028] In some embodiments of the present invention, the reactive group ratio of hyaluronic acid to short peptide in step S2 is (6-2):1.
[0029] In some preferred embodiments of the present invention, the reactive group ratio of hyaluronic acid to short peptide in step S2 is (5-3):1.
[0030] In some more preferred embodiments of the present invention, the reactive group ratio of hyaluronic acid to short peptide in step S2 is 4:1.
[0031] In some embodiments of the present invention, the mixing in step S2 includes the step of adding the short peptide solution dropwise into the hyaluronic acid solution.
[0032] In some embodiments of the present invention, the reaction conditions of the reaction solution in step S2 include: reacting at room temperature (20-30° C.) for 10-14 hours.
[0033] In some preferred embodiments of the present invention, the reaction conditions of the reaction solution in step S2 include: reacting at 20° C. for 12 hours.
[0034] In some embodiments of the present invention, the dialysis device used in the dialysis in step S3 includes: a dialysis bag, a dialysis tube, a dialysis barrel, and a dialysis sheet.
[0035] In some preferred embodiments of the present invention, the dialysis device used in the dialysis in step S3 is a dialysis bag.
[0036] In some more preferred embodiments of the present invention, the dialysis device used in the dialysis in step S3 is a dialysis bag with a molecular weight cutoff of 12 to 16 kDa.
[0037] In some more preferred embodiments of the present invention, the dialysis device used in the dialysis in step S3 is a dialysis bag with a molecular weight cutoff of 14 kDa.
[0038] In some embodiments of the present invention, step S3 further comprises the step of placing the dialysis device in boiling water for pretreatment for 5-15 minutes.
[0039] In some preferred embodiments of the present invention, step S3 further comprises the step of placing the dialysis device in boiling water for pretreatment for 10 minutes.
[0040] In some embodiments of the present invention, the dialysate used in the dialysis in step S3 includes N,N-dimethylformamide and deionized water.
[0041] In some preferred embodiments of the present invention, the dialysate used for the dialysis in step S3 further comprises a mixture of N,N-dimethylformamide and deionized water in a volume ratio of 1:2.
[0042] In some embodiments of the present invention, the dialysis described in step S3 includes: transferring the reaction solution to a dialysis device, using a mixture of N,N-dimethylformamide and deionized water in a volume ratio of 1:2 as the dialysis solution, dialyzing for 4 to 8 hours, and repeating the dialysis with changing the solution 2 to 4 times; then replacing the dialysis solution with deionized water, dialyzing for 20 to 28 hours, and repeating the dialysis with changing the solution 1 to 3 times.
[0043] In some preferred embodiments of the present invention, the dialysis described in step S3 includes: transferring the reaction solution to a dialysis device, using a mixture of N,N-dimethylformamide and deionized water in a volume ratio of 1:2 as the dialysis solution, dialysing for 6 hours, and repeating the dialysis with changing the solution for 3 times; then replacing the dialysis solution with deionized water, dialysis for 24 hours, and repeating the dialysis with changing the solution for 2 times.
[0044] In some embodiments of the present invention, step S3 further comprises the step of drying the obtained liquid phase.
[0045] In some preferred embodiments of the present invention, the drying includes freeze drying, normal pressure drying, reduced pressure drying, and spray drying.
[0046] In some more preferred embodiments of the present invention, the drying is freeze-drying.
[0047] According to a third aspect of the present invention, there is provided the use of the self-assembling polymer material according to the first aspect of the present invention and / or the self-assembling polymer material prepared by the preparation method according to the second aspect of the present invention in any one of (1) to (2):
[0048] (1) Preparation of self-assembled natural polymer nanofibers driven by short peptides;
[0049] (2) Preparation of polymer coatings for cell encapsulation.
[0050] In some embodiments of the present invention, the cells include prokaryotic cells, eukaryotic cells, mammalian cells, non-mammalian cells, stem cells, and combinations thereof.
[0051] In some preferred embodiments of the present invention, the cells are mesenchymal stem cells.
[0052] In some embodiments of the present invention, the polymer coating for encapsulating cells includes a hydrogel, a vesicle, or a semipermeable membrane.
[0053] In some preferred embodiments of the present invention, the polymer coating for encapsulating cells is a hydrogel.
[0054] According to a fourth aspect of the present invention, a self-assembled natural polymer nanofiber is provided, wherein the self-assembled natural polymer nanofiber is prepared from the self-assembled polymer material described in the first aspect of the present invention and / or the self-assembled polymer material prepared by the preparation method described in the second aspect of the present invention.
[0055] In some embodiments of the present invention, the method for preparing the self-assembled natural polymer nanofibers comprises the following steps: dissolving the self-assembled polymer in a buffer solution, adding an alkaline phosphatase solution, and obtaining the self-assembled natural polymer nanofibers after sufficient reaction.
[0056] In some preferred embodiments of the present invention, the buffer comprises: phosphate buffered saline (PBS) and Tris-HCl buffer (pH 8.0).
[0057] In some more preferred embodiments of the present invention, the buffer is: 0.01 mol / L PBS.
[0058] In some preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in the buffer solution is 0.05-1.5 wt %.
[0059] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in the buffer solution is 0.1-1 wt %.
[0060] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in the buffer solution is 0.25-1 wt %.
[0061] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in the buffer solution is 0.5-1 wt %.
[0062] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in the buffer solution is 0.75-1 wt %.
[0063] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in the buffer solution is: 1 wt %.
[0064] In some preferred embodiments of the present invention, the solvent of the alkaline phosphatase solution includes at least one of PBS, physiological saline and Tris-HCl buffer (pH 8.0).
[0065] In some more preferred embodiments of the present invention, the solvent of the alkaline phosphatase solution is Tris-HCl buffer (pH 8.0).
[0066] In some preferred embodiments of the present invention, the final concentration of the alkaline phosphatase solution in the reaction system is 0.05-0.2 U / mL.
[0067] In some more preferred embodiments of the present invention, the final concentration of the alkaline phosphatase solution in the reaction system is 0.1 U / mL.
[0068] In some preferred embodiments of the present invention, the conditions for sufficient reaction include: shaking the reaction at 35-39° C. and 500-700 rpm for 1-3 hours.
[0069] In some more preferred embodiments of the present invention, the sufficient reaction conditions include: shaking the reaction at 37° C. and 550-650 rpm for 2 hours.
[0070] In some more preferred embodiments of the present invention, the sufficient reaction conditions include: shaking the reaction at 37° C. and 600 rpm for 2 h.
[0071] In some preferred embodiments of the present invention, the method for preparing the self-assembled natural polymer nanofibers further comprises the step of adding an alcohol solvent to terminate the enzymatic reaction after sufficient reaction.
[0072] In some more preferred embodiments of the present invention, the method for preparing the self-assembled natural polymer nanofibers further comprises the step of adding methanol to terminate the enzymatic reaction after sufficient reaction.
[0073] According to a fifth aspect of the present invention, a polymer coating for cell encapsulation is provided, wherein the polymer coating for cell encapsulation is prepared from the self-assembled polymer material described in the first aspect of the present invention and / or the self-assembled polymer material prepared by the preparation method described in the second aspect of the present invention.
[0074] In some embodiments of the present invention, the cells include prokaryotic cells, eukaryotic cells, mammalian cells, non-mammalian cells, stem cells, and combinations thereof.
[0075] In some preferred embodiments of the present invention, the cells are mesenchymal stem cells.
[0076] In some embodiments of the present invention, the polymer coating for cell encapsulation includes a hydrogel, a vesicle, or a semipermeable membrane.
[0077] In some embodiments of the present invention, the method for preparing the polymer coating for cell encapsulation includes the following steps: dissolving the above-mentioned self-assembling polymer in a complete culture medium to obtain a mixed solution; adding the mixed solution to a cell culture system for incubation; removing the mixed solution, and then adding fresh complete culture medium and alkaline phosphatase solution for sufficient reaction; finally, aspirating the culture supernatant and washing the cells with a buffer solution to obtain the polymer coating for cell encapsulation.
[0078] In some preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in complete culture medium is 0.1-1.5 wt %.
[0079] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in complete culture medium is 0.25-1 wt %.
[0080] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in complete culture medium is 0.5-1 wt %.
[0081] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in complete culture medium is 0.75-1 wt %.
[0082] In some more preferred embodiments of the present invention, the final concentration of the self-assembling polymer after being dissolved in complete culture medium is 1 wt %.
[0083] In some preferred embodiments of the present invention, the complete culture medium comprises a basal culture medium and fetal bovine serum.
[0084] In some more preferred embodiments of the present invention, the basic culture medium includes: at least one of IMDM culture medium, BME culture medium, MEM culture medium, DMEM culture medium, Ham's F-12 culture medium, RPMI1640 culture medium, Fischer's culture medium, DMEM / F12 culture medium, and SCGM culture medium.
[0085] In some more preferred embodiments of the present invention, the basal culture medium is DMEM culture medium.
[0086] In some preferred embodiments of the present invention, the incubation conditions include incubating at 35-39° C. for 20-40 min.
[0087] In some more preferred embodiments of the present invention, the incubation conditions include incubating at 37°C for 30 min.
[0088] In some preferred embodiments of the present invention, the final concentration of the alkaline phosphatase solution in the reaction system is 0.05-0.2 U / mL.
[0089] In some more preferred embodiments of the present invention, the final concentration of the alkaline phosphatase solution in the reaction system is 0.1 U / mL.
[0090] In some preferred embodiments of the present invention, the conditions for sufficient reaction include: reacting at 35-39° C. for 0.5-2 h.
[0091] In some more preferred embodiments of the present invention, the sufficient reaction conditions include: reacting at 37° C. for 1 hour.
[0092] In some preferred embodiments of the present invention, the solvent of the alkaline phosphatase solution includes at least one of PBS, physiological saline and Tris-HCl buffer (pH 8.0).
[0093] In some more preferred embodiments of the present invention, the solvent of the alkaline phosphatase solution is Tris-HCl buffer (pH 8.0).
[0094] In some preferred embodiments of the present invention, the final concentration of the alkaline phosphatase solution in the reaction system is 0.05-0.2 U / mL.
[0095] In some more preferred embodiments of the present invention, the final concentration of the alkaline phosphatase solution in the reaction system is 0.1 U / mL.
[0096] In some preferred embodiments of the present invention, the buffer comprises PBS.
[0097] The present invention has at least the following beneficial effects:
[0098] The present invention provides a self-assembling polymer material, which is composed of a hyaluronic acid main chain and a short peptide side chain. The phosphate group on the tyrosine residue in the short peptide is cut by an external alkaline phosphatase to become a phenol structure, which enhances the strong interaction between the benzene rings, so that it spontaneously forms anisotropic nanofibers, which is used as a driving switch to trigger the self-assembly process, and pull the main chain hyaluronic acid group to form a mesh cross-linked structure. The self-assembly material provided by the present invention can be used to prepare a self-assembled natural polymer nanofiber driven by a short peptide and a hydrogel coating encapsulating mesenchymal stem cells. The natural polymer hyaluronic acid can specifically bind to the membrane protein CD44 on the surface of the mesenchymal stem cell, modify the polymer on the cell surface, and physically cross-link under the action of an external enzyme to form a polymer hydrogel structure. In addition, the raw materials used in the preparation process are all natural materials, have physiological compatibility, and the reaction process is under mild conditions, which is conducive to maintaining the normal function and vitality of the cell, and is used for further engineering modification, and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0099] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0100] Figure 1 is a synthetic route diagram of the self-assembling polymer material in Example 1 of the present invention;
[0101] Figure 2 This is a schematic diagram of the process of preparing a hydrogel coating on the surface of MSCs using a self-assembling polymer material in Example 8 of the present invention;
[0102] Figure 3 The synthetic modification pathway diagram of the Rhodamine B fluorescent molecule used in Example 8 of the present invention;
[0103] Figure 4 This is the hydrogen nuclear magnetic resonance spectrum of the amino-modified rhodamine B fluorescent molecule used in Example 8 of the present invention;
[0104] Figure 5 are nuclear magnetic resonance hydrogen spectra of Examples 1-3 in the test examples of the present invention, wherein A is Example 1, B is Example 2, and C is Example 3;
[0105] Figure 6 The TEM results of the nanofibers in the negative control group and Example 4 in the test examples of the present invention are shown, wherein the -ALP group is the negative control group, the +ALP group is Example 4, and the scale is 500 nm;
[0106] Figure 7 The SEM results of the self-assembled polymer materials of Examples 1-3 in the test examples of the present invention after being prepared into nanofibers, wherein A is Example 1, B is Example 2, and C is Example 3, and the scale is 20 μm;
[0107] Figure 8 This is a graph showing the elastic modulus results of the self-assembled hydrogels prepared in Examples 5-7 of the test examples of the present invention;
[0108] Fig. 9 The fluorescence imaging images of the hydrogel coating in situ encapsulated on the cell surface prepared in the control group and Example 8 in the test examples of the present invention, wherein the MSC group is the control group and the MSC@Polymer group is Example 8, and the scale is 30 μm;
[0109] Fig.10 The SEM results of the cell surface hydrogel coating prepared in the control group and Example 9 in the test example of the present invention, wherein the MSC group is the control group, and the MSC@P group is Example 9, and the scale is 10 μm;
[0110] Fig.11 This is a result diagram of the cell viability test after MSCs were treated with the self-assembled polymer material prepared in Examples 1-3 of the test examples of the present invention. DETAILED DESCRIPTION
[0111] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0112] Example 1
[0113] This embodiment provides a self-assembling polymer material, the synthesis path is as follows Figure 1 As shown, the specific preparation method comprises the following steps:
[0114] 1) Design the sequence of short peptide side chains and synthesize the corresponding peptide segments:
[0115] Phenylalanine (F)-phenylalanine (F) was used as the self-assembly motif, and lysine (K) was connected to one end to modify the active functional group amino group, and tyrosine (Y) was connected to the outer end while the phosphate group (p) was modified on the residue; in order to increase the intermolecular force, a naphthalene group was modified on the other end to increase the interaction between aromatic groups, and the short peptide sequence Nap-FFK-Yp was designed. The short peptide sequence was commissioned to be artificially synthesized by Wang Huaimin's research group at West Lake University;
[0116] 2) Weigh 50 mg (1 eq.) of HA (Mw = 150 kDa) powder, dissolve it in 15 mL of formamide, and stir at 50 °C for 1 h until the solution becomes clear;
[0117] 3) Weigh 28.8 mg (1.5 eq.) of EDC and 21.4 mg (1.5 eq.) of NHS, add them to the solution obtained in step 2), and react at 0° C. for 30 min to obtain a HA solution;
[0118] 4) Weigh 35 mg of the short peptide (Mw=851.33 g / mol) obtained in step 1) and dissolve it in 15 mL of N,N-dimethylformamide. Mix well. Add the N,N-dimethylformamide solution containing the peptide dropwise into the HA solution. React at room temperature for 12 h to obtain a reaction solution.
[0119] 5) Prepare a dialysis bag with a molecular weight cut-off of 14 kDa and pretreat it in boiling water for 10 min;
[0120] 6) After the reaction is completed, the reaction solution is transferred to a dialysis bag. The dialysis solution is a mixture of N, N-dimethylformamide and deionized water in a volume ratio of 1:2. The solution is changed three times during the dialysis process, and each dialysis lasts for 6 hours. Then, the dialysis solution is replaced with deionized water. The solution is changed twice during the dialysis process, and each dialysis lasts for 24 hours.
[0121] 7) After the dialysis is completed, the liquid phase is collected and freeze-dried to obtain a white solid, i.e., the self-assembled polymer material, which is weighed and stored at 4°C.
[0122] Example 2
[0123] This embodiment provides a self-assembling polymer material, and the specific preparation method is different from that of Example 1 only in that the mass of the short peptide used is 26.3 mg.
[0124] Example 3
[0125] This embodiment provides a self-assembling polymer material, and the specific preparation method is different from that of Example 1 only in that the mass of the short peptide used is 15 mg.
[0126] Example 4
[0127] This embodiment provides a self-assembled natural polymer nanofiber, using the self-assembled polymer material prepared in Example 2, and inducing the self-assembled polymer material to form a porous network structure by adding alkaline phosphatase. The specific preparation method includes the following steps:
[0128] 1) Weigh 10 mg of the self-assembling polymer material prepared in Example 2, dissolve it in 10 mL of PBS, and the concentration of the resulting solution is 0.1 wt %. Take 400 μL into a 1.5 mL centrifuge tube;
[0129] 2) Add 1U of alkaline phosphatase (ALP) solution to a Tris-HCl (pH 8.0) buffer solution to obtain a final concentration of 10U / mL to obtain an ALP stock solution;
[0130] 3) Add 4 μL of the ALP stock solution obtained in step 2) to a 1.5 mL centrifuge tube to make the concentration of ALP in the system 0.1 U / mL, mix well, and react in an oscillating metal bath at 37°C and 600 rpm (550-650 rpm is acceptable) for 2 h;
[0131] 4) At the end of the reaction, 40 μL of methanol was added to terminate the enzymatic reaction, thereby obtaining self-assembled natural polymer nanofibers.
[0132] Example 5
[0133] This embodiment provides a self-assembled hydrogel, and the specific preparation method includes the following steps:
[0134] 1) Weigh 10 mg of the self-assembling polymer material prepared in Example 1, dissolve it in PBS to make the final concentrations of 0.25 wt%, 0.5 wt%, 0.75 wt% and 1 wt%, respectively, and take 200 μL into four 1.5 mL centrifuge tubes respectively;
[0135] 2) Add 1U of alkaline phosphatase (ALP) solution to a Tris-HCl (pH 8.0) buffer solution to obtain a final concentration of 10U / mL to obtain an ALP stock solution;
[0136] 3) Add 2 μL of the ALP stock solution obtained in step 2) to each 1.5 mL centrifuge tube to make the concentration of ALP in the system 0.1 U / mL. After mixing, add the mixed solution into the gel-forming mold and wait for it to solidify to prepare self-assembled hydrogels containing self-assembled polymer materials of different concentrations.
[0137] Example 6
[0138] This embodiment provides a self-assembled hydrogel, and the specific preparation method includes the following steps:
[0139] 1) Weigh 10 mg of the self-assembling polymer material prepared in Example 2, dissolve it in deionized water to make the final concentrations 0.25 wt%, 0.5 wt%, 0.75 wt% and 1 wt%, respectively, and take 200 μL into four 1.5 mL centrifuge tubes respectively;
[0140] 2) Add 1U of alkaline phosphatase (ALP) solution to a Tris-HCl (pH 8.0) buffer solution to obtain a final concentration of 10U / mL to obtain an ALP stock solution;
[0141] 3) Add 2 μL of the ALP stock solution obtained in step 2) to each 1.5 mL centrifuge tube to make the concentration of ALP in the system 0.1 U / mL. After mixing, add the mixed solution into the gel-forming mold and wait for it to solidify to prepare self-assembled hydrogels containing self-assembled polymer materials of different concentrations.
[0142] Example 7
[0143] This embodiment provides a self-assembled hydrogel, and the specific preparation method includes the following steps:
[0144] 1) Weigh 10 mg of the self-assembling polymer material prepared in Example 3, dissolve it in deionized water to make the final concentrations 0.25 wt%, 0.5 wt%, 0.75 wt% and 1 wt%, respectively, and take 200 μL into four 1.5 mL centrifuge tubes respectively;
[0145] 2) Add 1U of alkaline phosphatase (ALP) solution to a Tris-HCl (pH 8.0) buffer solution to obtain a final concentration of 10U / mL to obtain an ALP stock solution;
[0146] 3) Add 2 μL of the ALP stock solution obtained in step 2) to each 1.5 mL centrifuge tube to make the concentration of ALP in the system 0.1 U / mL. After mixing, add the mixed solution into the gel-forming mold and wait for it to solidify to prepare self-assembled hydrogels containing self-assembled polymer materials of different concentrations.
[0147] Example 8
[0148] In this example, the self-assembled polymer material prepared in Example 2 was used to prepare a hydrogel coating for in situ encapsulation on the cell surface. The preparation process is as follows: Figure 2 As shown, the specific steps include:
[0149] 1) Weigh 30 mg (1 eq.) of the self-assembled polymer material prepared in Example 2, dissolve it in 20 mL of deionized water, stir and dissolve, then add 17.2 mg EDC (1.5 eq.) and 13 mg NHS (1.5 eq.), place in a 0°C ice water bath and stir for 30 min; then add 40 mg of amino-modified rhodamine B fluorescent molecule (1 eq.), the synthetic modification route of rhodamine B fluorescent molecule is as follows: Figure 3 As shown, the nuclear magnetic resonance hydrogen spectrum of the obtained amino-modified rhodamine B fluorescent molecule is as follows Figure 4 As shown; stirring to dissolve, reacting at room temperature for 24 hours; after the reaction, transferring the reaction solution to a dialysis bag with a molecular weight cutoff of 14 kDa for dialysis, the dialysis solution is deionized water, the dialysis is performed for 48 hours, and the solution is changed every 12 hours; after the dialysis is completed, freeze drying is performed to obtain a self-assembled polymer material modified with rhodamine B;
[0150] 2) Weigh 2.25 mg of the self-assembling polymer material modified with rhodamine B prepared in step 1), dissolve it in 900 μL of DMEM complete medium (90% DMEM + 10% fetal bovine serum), mix well, and filter through a 0.22 μm filter membrane to obtain a clear sterile liquid with a final concentration of 0.25 wt%;
[0151] 3) Cell culture: 2×10 4 Mesenchymal stem cells (MSCs) were resuspended in 300 μL DMEM complete medium and added to an ibidi eight-well chamber with a glass slide at the bottom of the chamber. They were cultured in an incubator at 37°C for 24 h, the culture supernatant was discarded, and the cells were washed twice with PBS buffer;
[0152] 4) 300 μL of the clear sterile liquid obtained in step 1) was added to the well chamber for 30 min, so that the polymer can be adsorbed on the cell membrane by virtue of the transient binding of the polymer to the cell surface protein;
[0153] 5) Discard the supernatant, add 300 μL of fresh DMEM complete medium, and then add 3 μL of 10 U / mL ALP stock solution, mix well to make the final ALP concentration in the reaction system 0.1 U / mL, and react in a 5% carbon dioxide incubator at 37°C for 1 hour;
[0154] 6) After the reaction is completed, the supernatant is discarded and the cells are washed twice with PBS buffer to obtain a hydrogel coating encapsulated in situ on the cell surface.
[0155] Example 9
[0156] In this example, the self-assembled polymer material prepared in Example 2 was used to prepare a hydrogel coating for in situ encapsulation on the cell surface. The specific steps were different from those in Example 8 only in the conditions for cell inoculation: In this example, 1×105 MSCs were seeded in a 48-well plate covered with an 8 mm cell slide, and the culture system was 300 μL.
[0157] Test Case
[0158] This test example tested the performance of the self-assembled polymer materials prepared in Examples 1-3, the self-assembled natural polymer nanofibers prepared in Example 4, the self-assembled hydrogels prepared in Examples 5-7, and the hydrogel coatings encapsulated in situ on the cell surface prepared in Examples 8-9, including the following test items: polymer material grafting efficiency, polymer material unit mass ratio, TEM and SEM characterization of nanofibers, hydrogel mechanical strength, fluorescence and SEM characterization of cell surface hydrogel coatings, and cell viability test. The specific test steps and test results are as follows:
[0159] 1. Grafting efficiency test of self-assembled polymer materials:
[0160] 1 mg of the self-assembled polymer material prepared in Examples 1-3 was weighed and dissolved in 500 μL DMSO-d6. The grafting efficiency was calculated by nuclear magnetic resonance spectroscopy. The nuclear magnetic resonance spectrometer used was from Bruker, AC (400 MHz). The obtained nuclear magnetic resonance spectroscopy was as follows: Figure 5 As shown, the specific calculation formula is:
[0161] The calculated grafting efficiency is: 33% for Example 1, 20% for Example 2, and 13% for Example 3.
[0162] 2. Calculation of unit mass ratio of self-assembled polymer materials:
[0163] Taking Example 2 as an example to calculate the unit mass ratio of the self-assembled polymer material, the molar ratio of the HA repeating unit to the short peptide is 5:1, calculated by the short peptide grafting rate. The unit mass ratio of the self-assembled polymer material is calculated as follows:
[0164] HA mass ratio:
[0165] Mass proportion of short peptides:
[0166] 3. TEM and SEM characterization of nanofibers:
[0167] 1) TEM sample preparation steps:
[0168] ① Take 100 μL of the self-assembled polymer material solution prepared in Example 2 (the self-assembled polymer material is dissolved in deionized water to obtain a self-assembled polymer material solution with a concentration of 0.1 wt%, i.e., the negative control group) and the self-assembled natural polymer nanofiber prepared in Example 4 (i.e., the experimental group) and drop them on a 200-mesh copper grid, and place the samples under a heat light source for drying;
[0169] ② Add 20 μL of 2% uranyl acetate solution to the dried sample and stain for 15 minutes;
[0170] ③ Wash the copper mesh with deionized water for 5 minutes each time, repeat three times, and remove the water at the other end of the copper mesh with absorbent paper after washing;
[0171] ④ Place the sample under a heat source to dry, and load it onto the TEM loading platform for observation and photography. The results are as follows: Figure 6 shown.
[0172] Depend on Figure 6 It can be seen that the negative control group did not add ALP solution, and the self-assembled polymer material could not form a porous network structure; after ALP was added in Example 4, ALP removed the side phosphate group on tyrosine, enhanced the π-π stacking effect of the aromatic molecules, and at the same time, the large conjugated benzene ring structure of the naphthalene group further promoted the skeleton strength of the polypeptide aggregates, causing the main chain hyaluronic acid to orient, and the fibers formed by the side chain polypeptides were entangled with each other, and entanglement also occurred between different polymer main chains, eventually forming a complex physical cross-linked network.
[0173] 2) SEM sample preparation steps:
[0174] ① Weigh 1 mg of the self-assembling polymer material prepared in Example 1-3 and dissolve it in 500 μL DMSO-d6 to prepare the self-assembling polymer material solutions prepared in Example 1-3 respectively, take 100 μL of each and put it into three 1.5 mL centrifuge tubes respectively, place them at -80°C to cool for 1 hour, and then move them into a freeze dryer for vacuum treatment, and obtain white powder after 2 hours;
[0175] ② Move the white powder onto the sample stage, spray gold on the sample, observe the sample morphology under a scanning electron microscope and take photos. The results are as follows: Figure 7 shown.
[0176] Depend on Figure 7 It can be seen that the self-assembled polymer materials prepared in Examples 1-3 can form a network cross-linked structure after adding ALP.
[0177] 4. Test on the effect of different concentrations of self-assembled polymer materials on the mechanical strength after gelation:
[0178] The self-assembled hydrogel samples of different concentrations obtained in Examples 5-7 were extruded from the mold to the sample stage of the rheometer, and the frequency was set to 1 Hz to test the mechanical properties of the gel. The results are shown in FIG. Figure 8 shown.
[0179] Depend on Figure 8 It can be seen that the hydrogels prepared in Examples 5-7 of the present invention have excellent mechanical strength, are not easily deformed under the action of external forces, and their elastic modulus increases with the increase in the concentration of the self-assembling polymer material used.
[0180] 5. Fluorescence imaging of hydrogel coating on cell surface:
[0181] 1) Add 300 μL of 4% paraformaldehyde to the ibidi eight-well chamber containing the cells of Example 8 and only containing MSCs (the cell inoculation and culture steps are exactly the same as those of Example 8, i.e., the control group) and fix them at room temperature for 10 min. After treatment, wash the cells with PBS;
[0182] 2) After washing, the samples were stained with 5 μM DiD dye for 6 min, washed with PBS, then stained with 0.1 mg / mL Congo Red dye for 20 min, and washed three times with PBS;
[0183] 3) The cell sample prepared by the above process was used as the observation object, and the prepared cell sample was photographed and imaged by laser confocal microscope (Zeiss LSM 880), and 488nm, 543nm and 643nm lasers were used for scanning imaging; the 643nm laser channel imaged the cell membrane position, adjusted the voltage and laser intensity, found the appropriate focal plane position, and photographed; the 543nm laser channel observed the fluorescence signal of rhodamine, thereby imaging the HA position, adjusted the voltage and laser intensity, and photographed; the 488nm laser channel imaged the nanofiber position, adjusted the voltage and laser intensity, and photographed. The results are shown in FIG. Fig. 9 shown.
[0184] Congo Red dye can specifically stain the β structure of self-assembled nanofibers, Rhodamine B signal is used to locate HA, and DiD dye is lipophilic and can be used to mark cell membranes. Fig. 9 It can be seen that the laser confocal microscopy imaging of Example 8 found that the rhodamine B signal and the cell membrane signal (DiD) were co-localized, indicating that HA was successfully targeted on the cell membrane, and Congo red staining proved that the self-assembly of polypeptides induced hyaluronic acid to self-assemble, and the formed nanofibers were wrapped on the cell surface to form a cross-linked network to form a hydrogel.
[0185] 6. SEM imaging of cell surface hydrogel coating:
[0186] 1) The slides prepared in Example 9 and the slides inoculated with an equal amount of MSCs (the culture steps were exactly the same as in Example 9, i.e., the control group) were transferred to liquid nitrogen for cooling for 5 seconds and freeze-dried overnight for dehydration;
[0187] 2) The sample was gold-sprayed to a thickness of 2 nm, and the cell sample image was observed by high-power field emission scanning electron microscopy. The results were as follows: Fig.10 shown.
[0188] Depend on Fig.10 It can be seen that the SEM image of Example 9 shows a clear reticular structure encapsulating the cells, while the control group does not have such a structure, indicating that the polymer material prepared by the present invention can self-assemble under the condition of external addition of ALP to form a hydrogel coating that encapsulates cells.
[0189] 7. Cell viability test:
[0190] 1) 5000 MSCs were resuspended in 100 μL DMEM complete medium and seeded into 96-well plates for 24 h;
[0191] 2) Weigh the polymer materials prepared in Examples 1-3 respectively, dissolve them in DMEM complete medium, adjust the final concentrations of the self-assembling polymer materials in the medium to 0.25wt%, 0.5wt%, 0.75wt%, and 1wt%, respectively, take 100 μL of each and add them to a 96-well plate, and incubate for 1 hour;
[0192] 3) Discard the culture supernatant and add 100 μL of DMEM complete medium containing 0.1 U / mL ALP to each well and react for 1 hour;
[0193] 4) After the reaction, the old culture medium was removed, the plate was washed twice with 1×PBS, the supernatant was discarded, and DMEM solution containing 10% CCK8 (v / v%) was added, and incubated at 37°C for 3 h. The absorbance at 450 nm was then measured by a multifunctional microplate reader to characterize cell viability. The results are shown in Fig.11 shown.
[0194] Depend on Fig.11 It can be seen that the polymer material prepared by the present invention has little effect on the cell viability of MSCs, and the material has high biocompatibility. The strategy of using side chain self-assembling polypeptides to induce the main chain natural polymer to form a nano-crosslinked network structure hydrogel to complete cell encapsulation is more conducive to the cells to exert their functions due to the mild processing process, good biocompatibility of raw materials and simple operation process.
[0195] This invention is supported by the National Key R&D Program of China (2022YFB3808300).
[0196] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A self-assembling polymer material, characterized in that: Comprising a hyaluronic acid main chain and short peptide side chains, the structural formula of the self-assembling polymer material is as follows: Among them, 248≤m≤319, 53≤n≤124; The preparation method of the self-assembling polymer material comprises the following steps: S1: dissolving hyaluronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide in a solvent and reacting them sufficiently to obtain a hyaluronic acid solution; S2: mixing the short peptide solution and the hyaluronic acid solution obtained in step S1 to obtain a reaction solution; S3: dialyzing the reaction solution obtained in step S2, and collecting the liquid phase obtained after dialysis, which is the self-assembled polymer material; The structure of the short peptide in step S2 includes: naphthalene-phenylalanine-phenylalanine-lysine-phosphorylated tyrosine residue.
2. The self-assembling polymer material according to claim 1, characterized in that In step S1, the molar ratio of hyaluronic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 1:(1-2):(1-2).
3. The self-assembling polymer material according to claim 1, characterized in that In step S2, the reactive group ratio of hyaluronic acid to short peptide is (6-2):
1.
4. The self-assembling polymer material according to claim 1, characterized in that The solvent in step S1 includes formamide.
5. The self-assembling polymer material according to claim 1, characterized in that: The dialysate used in the dialysis in step S3 includes N,N-dimethylformamide and deionized water.
6. Use of the self-assembling polymer material as claimed in any one of claims 1 to 5 in any one of (1) to (2): (1) Preparation of self-assembled natural polymer nanofibers driven by short peptides; (2) Preparation of polymer coatings for cell encapsulation.
7. A self-assembled natural polymer nanofiber, characterized in that: The self-assembled natural polymer nanofiber is prepared from the self-assembled polymer material described in any one of claims 1 to 5.
8. A polymer coating for cell encapsulation, characterized in that: The polymer coating is prepared from the self-assembling polymer material described in any one of claims 1 to 5.